KOMPLEKSITAS PENANGANAN PENGUATAN KETAHANAN PANGAN - Rustan A., S, Tri Noor Aziza, SP, MP dan (Jurnal Borneo Administrator, 2008)
Food resilience as an especial system taken as as prosperity measuring rod a nation, requiring complex handling by entangling all subsistem having an effect on.  In order not to to food crisis, totality strategy supporter of reinforcement of food resilience need optimise of role and function. UU No. 7 Year 1996 about food commend the importance of attention to make-up of food resilience utilize to realize secure and prosperous Indonesia society, prosperous, with quality, and competitive.  Keywords : Penguatan, Ketahanan Pangan